The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/er.6410
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐objective economic dispatch of power system with wind farm considering flexible load response

Abstract: The uncertainty of wind farm power and load both have a certain impact on the economic dispatch of the power system. First, this study deals with the fuzzy processing of power prediction error and load forecasting error of wind farms based on fuzzy random theory. On this basis, a multi-objective fuzzy stochastic dispatch model of a power system with flexible load is established under the carbon trading mechanism. And, the nonlinear cost of flexible load response and the cost of carbon emission compensation is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
(18 reference statements)
0
5
0
Order By: Relevance
“…A renewable energy quota system and its supporting green certificate trading mechanism can be designed in the power generation side, and the game model is established, and the designed mechanism is simulated and analyzed [7] . Some scholars have built a multi-objective dynamic environmental economic scheduling model of wind farm power system based on green certificate trading mechanism, proposed a multi-objective algorithm based on reverse learning chaotic search, and obtained the advantages of green certificate trading mechanism [8] . At the same time, relevant studies combined blockchain technology and green certificate trading mechanism, proposed a comprehensive energy system optimization model including green certificate cross-chain transaction, and concluded that green certificate trading mechanism can reduce system operating costs and promote the consumption of renewable energy [9] .…”
Section: Introductionmentioning
confidence: 99%
“…A renewable energy quota system and its supporting green certificate trading mechanism can be designed in the power generation side, and the game model is established, and the designed mechanism is simulated and analyzed [7] . Some scholars have built a multi-objective dynamic environmental economic scheduling model of wind farm power system based on green certificate trading mechanism, proposed a multi-objective algorithm based on reverse learning chaotic search, and obtained the advantages of green certificate trading mechanism [8] . At the same time, relevant studies combined blockchain technology and green certificate trading mechanism, proposed a comprehensive energy system optimization model including green certificate cross-chain transaction, and concluded that green certificate trading mechanism can reduce system operating costs and promote the consumption of renewable energy [9] .…”
Section: Introductionmentioning
confidence: 99%
“…In [36], the authors have used an improved simplex based PSO for solving CEED. In [37], authors have modelled the ELD problem in presence of wind farms and flexible resources in a multi-objective framework and solved the problem by fuzzy logic. In [38], the authors have used MFO algorithm for solving ELD for integrated power system in presence of stochastic wind generation.…”
Section: Introductionmentioning
confidence: 99%
“…One of the contingencies that can easily imperil the energy system's security is the uncertainty of forecasted data, which originate from the unpredicted altering of injected power to the system by renewable sources, loads, and short-term electricity trades. 9 In this regard, authors of [10][11][12][13][14][15] aim at enhancing the security of energy systems besides considering uncertainties. In Reference 10, a distributed robust formulation for chance constraints of the SCOPF problem is proposed based on optimal probability constraints.…”
Section: Introductionmentioning
confidence: 99%